(untitled) (Eurasian Journal of Ecology, 2022)
Environmental awareness issues in Kazakhstan are one of the most undermined topics both among the public community and in terms of state rhetoric. In the context of official state documents, so far only two official environmental codes and national program called Zhasyl Kazakhstan were introduced in the country in 2021. While on the one hand the Environmental Code was introduced with the purpose to modernize, frame and enlist main legislative aspects on various sectors of environmental law in Kazakhstan, on the other hand the Zhasyl Kazakhstan Program has been implemented as a state program to address with numerous environmental projects various environmental issues ranging from air pollution to waste management as well as aspects related to ecological education and low environmental awareness matters. In this regard, the main goal of this paper is to analyze critically the main content of both of these documents with a particular focus on sections related to environmental awareness raising aspects. For that, this paper applied a subjective-based content analysis in order to identify interesting insights on regulatory legal aspects, future research streams, and uncovering of improved legislative frameworks in the context of environmental awareness issue. Apart from that, five open-ended questions were send out to the Ministry of Ecology, Geology and Natural Resources to obtain primary data on the state’s view in regards to current previous, recent and future aspects of environmental awareness issue in the country. Key words: Kazakhstan, environmental awareness, Environmental Code, Zhasyl Kazakhstan, content analysis.